2010
DOI: 10.1111/j.1532-7795.2010.00645.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of Mathematics Interest in Adolescence: Influences of Gender, Family, and School Context

Abstract: This study investigated adolescents' developmental trajectories of mathematics interest and explored related effects of gender, family, and school context. Latent growth curve modeling was used to analyze longitudinal data of N 5 3,193 students (51% female) from grades 5 to 9 from all 3 ability tracks of the German state school system. Annual assessments involved student questionnaires on interest in mathematics, perceptions of classroom characteristics (classroom values for mathematics, mathematics teacher en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
325
4
35

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 375 publications
(381 citation statements)
references
References 66 publications
17
325
4
35
Order By: Relevance
“…Previous studies revealed that gender has been shown to be related to learning environment perceptions [52] as well as to mathematics self-concept and interest [10,53]. Ditton [19], for example, showed that male students evaluate their mathematics teachers' performance more positively than their female classmates.…”
Section: Characteristics Of Instructional Quality Mathematics Self-comentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies revealed that gender has been shown to be related to learning environment perceptions [52] as well as to mathematics self-concept and interest [10,53]. Ditton [19], for example, showed that male students evaluate their mathematics teachers' performance more positively than their female classmates.…”
Section: Characteristics Of Instructional Quality Mathematics Self-comentioning
confidence: 99%
“…Results do not indicate whether students' learning outcomes or other relevant factors impact the pattern of perceived instructional quality to which they belong or vice versa. As suggested by previous longitudinal analyses [10,16], it was assumed that attitudinal and affective learning characteristics differ depending on students' perceived instructional quality. However, longitudinal studies are needed to conclusively determine the direction of influence.…”
Section: Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, the commonality of curriculum, norms of practice, and societal norms over time yield a smaller set of long-term engagement patterns. Individual interest, exogenous instrumentality, goal orientations, and broader academic self-efficacy currently tend to lessen learners' enjoyment of and persistence in challenging mathematics as they grow older (Frenzel et al 2010;Mangu et al 2015;Watt 2004;Fredricks and Eccles 2002).…”
Section: Summary and Looking Aheadmentioning
confidence: 99%